SAT0739-HPR Patients' preferences toward characteristics of treatment with biological agents differ according to experience with their rheumatic disease and treatment received or prescribed: results from the cara study. (15th June 2017) - Sinigaglia, L; Sarzi-Puttini, P; Scalone, L; Montecucco, CM; Giacomelli, R; Lapadula, G; Olivieri, I; Giardino, A; Cortesi, P; Mantovani, LG; Mecchia, M; ,
Abstract : Background: The development of biologic therapies has created a more complex decision-making process to select the treatment option for patients. In order to optimize the appropriateness of the decisions, it is necessary to be informed and aware of the preferences of the interested parties and the influence of their experiences on their preferences for the different treatments. Objectives: To estimate preferences of relevant treatment characteristics valued by the different subjects involved in the management of patients with rheumatic diseases. This abstract focuses on patients' preferences. Methods: We involved patients with rheumatoid arthritis ( RA ), ankylosing spondylitis ( AS ) or psoriatic arthritis ( PsA ), who according to clinical practice, at the time of data collection had for the first time a prescription of ( naïve ), or received treatment with ( experienced ) biological drugs for at least 3 months in the last 12 months. Through a Discrete-Choice-Experiment, the participants valued 16 possible scenarios in which pairs of similarly effective treatments were described with 6 characteristics including 2–4 possible levels each: (1) frequency of administration; (2) mode and place of administration; (3) hospitality, service, efficiency and courtesy of health personnel; (4) frequency of reactions at the site of drug administration; (5) generalized undesired reactions or allergic reactions involving the whole body; (6) additional contribution added as healthcare taxes to be paid by all the citizens to make available the treatment to target patients. Results: 513 patients from 30 centres through Italy participated, balanced for diagnosis and treatment experience (around 20% of each subgroup). Characteristics 4, 3 and 6 were the first, second and third most important ones for every subgroup, the fourth most important characteristic was 1 ( experienced RA ), 5 ( naïve AS ), and 2 for the other subgroups. Across all the subgroups, patients generally preferred very satisfactory levels of (3), infrequent (4), mild (5), and no (6). Instead, for characteristics (1) and (2) the patients generally preferred the frequency, mode and place of administration that were closer to those actually experienced or prescribed. Conclusions: Taking into account the different opinions of patients on at least some treatment characteristics could guide the conduction of good choices aimed to optimize benefits and to allocate efficiently resources. Disclosure of Interest: L. Sinigaglia: None declared, P. Sarzi-Puttini: None declared, L. Scalone: None declared, C. Montecucco: None declared, R. Giacomelli Grant/research support from: MSD, G. Lapadula: None declared, I. Olivieri: None declared, A. Giardino Employee of: MSD Italia, P. Cortesi Grant/research support from: Gilead, L. Mantovani: None declared, M. Mecchia Employee of: MSD Italia